Analyzing the role of malnourishment in malocclusion: A cross-sectional study - Kumar Anand; Kumari Menka; Saritha Maloth; Subhash Chandra Nayak; Tina Chowdhary; Manish Bhargava (Wolters Kluwer Medknow Publications, 2021)
Background: Malocclusion is defined as an occlusion in which there is malrelationship between the arches in any of the three planes or anomalies in tooth position beyond normal limits, the etiology being multifactorial. Malnutrition may also be allied to malocclusion, predominantly crowding, due to insufficient space for the teeth to erupt in the correct place. Objectives: The present study was conducted to investigate the role of diet as an etiological factor in the occurrence of malocclusion. Materials and Methods: Two hundred and twenty malnourished subjects were examined by a single experienced dental professional and the occlusal relationships were evaluated at a centric occlusion position by instructing the subject to swallow and then bite on the teeth together. Results: Ninety-eight subjects (44.54%) had Angle's Class I malocclusion with crowding: 18 (8.1%) presented with spacing. Angle's Class II division 1 malocclusion was evident in 52 subjects (23.63%), while Class II division 2 in 38 subjects (17.27%). Only 14 subjects (6.3%) presented with Angle's class III malocclusion. Conclusion: Dietary factors and dentition measures from a subset 220 malnourished subjects found that malnourished subjects with basal metabolic index <18.5 had statistically significant relationships with the crowding variables.